An Economic Analysis of the Fuel Oil Situation - Arthur Knapp (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1928)
THE economics of fuel oil must be considered in two aspects; viz., fuel oil as one of a number of competitive fuels and fuel oil as a refined product of petroleum. "Fuel Oil" is usually defined as that product of petroleum which is used in furnaces for the generation of heat by simple combustion. It is true that any product of petroleum used in an internal combustion engine is essentially a fuel oil, but such oils are not included in the class known as "Fuel Oil." FUEL OIL AS ONE OF SEVERAL FUELS For a number of years, the petroleum industry has believed that the petroleum reserves were very limited and that petroleum products would begin to become scarce within a few years. The industry has believed FIG. 1.-DAILY AVERAGE CONSUMPTION OF FUELS BY PUBLIC UTILITY POWER PLANTS. that there would be a gradual but continual rise in prices as a result of this impending scarcity.